The MD and the DRG - Morreim, E. Haavi (The Hastings Center report, 1985)
As they struggle to maintain high-quality health care in the face of new economic limitations, physicians should not endanger their relationships with patients. But they should collectively revise the informal protocols that guide clinical decision making.